The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/sia.1652
|View full text |Cite
|
Sign up to set email alerts
|

Development of cerium‐based conversion coatings on 2024‐T3 Al alloy after rare‐earth desmutting

Abstract: The deposition of Ce-based conversion coatings onto 2024-T3 Al alloy sheet was studied using Rutherford backscattering spectroscopy, scanning electron microscopy, Auger electron spectroscopy, x-ray photoelectron spectroscopy and atomic force microscopy. The Al sheet was pretreated with an alkaline clean followed by treatment in a Ce(IV) and H 2 SO 4 -based desmutter. The Ce(IV)-based conversion coating solution contained 0.1 M CeCl 3 ·7H 2 O and 3% H 2 O 2 and was acidified to pH 1.9 with HCl. Upon immersion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 20 publications
2
85
0
Order By: Relevance
“…95 Buchheit et al 103 used Zn-Al layered double hydroxides (LDHs) as containers for inhibiting decavanadate ions (V 10 O 28 6-), within epoxy coatings upon AA2024-T3. It was observed that firstly, decavanadate ions Several studies demonstrated the presence of Cr(VI) within the conversion coating 45,46 Suspected to be carcinogenic 50 RE-based (Ce or La) AA2024-T3 57,58,63 Mainly works as cathodic inhibitors, precipitation of Ce-oxide on cathodic sites, induced by the local pH increase Vulnerability of RE market as mainly dominated by Chinese production 66,67 Galvanized steel 62 Only minor improvement in pitting potential and corrosion current was noted 56,65 Vanadate-based AA2024-T3 zinc carbon steel 69 Adsorption of inhibitor on cathodic sites (intermetallic particles in the case of AA2024-T3) and stabilization of passive film. Inhibition of oxygen reduction reaction [20][21][22]70 Do not meet environmental and health restrictions as Vanadium and its compounds were proven to be carcinogenic [72][73][74] Li-containing Only tested on AA2024-T3 Good barrier properties provided by both systems Organic: effective inhibitor is still needed to achieve good corrosion resistance Nanocomposites: higher density of inhibitor can be loaded into the system Nanocomposites: cost towards implementation could be too important 99,100 Phosphate-based Steel carbon steel Al alloys zinc were controllably released from the LDH containers and also that the aggressive chloride ions were also entrapped within such containers.…”
Section: Lithium-containing Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…95 Buchheit et al 103 used Zn-Al layered double hydroxides (LDHs) as containers for inhibiting decavanadate ions (V 10 O 28 6-), within epoxy coatings upon AA2024-T3. It was observed that firstly, decavanadate ions Several studies demonstrated the presence of Cr(VI) within the conversion coating 45,46 Suspected to be carcinogenic 50 RE-based (Ce or La) AA2024-T3 57,58,63 Mainly works as cathodic inhibitors, precipitation of Ce-oxide on cathodic sites, induced by the local pH increase Vulnerability of RE market as mainly dominated by Chinese production 66,67 Galvanized steel 62 Only minor improvement in pitting potential and corrosion current was noted 56,65 Vanadate-based AA2024-T3 zinc carbon steel 69 Adsorption of inhibitor on cathodic sites (intermetallic particles in the case of AA2024-T3) and stabilization of passive film. Inhibition of oxygen reduction reaction [20][21][22]70 Do not meet environmental and health restrictions as Vanadium and its compounds were proven to be carcinogenic [72][73][74] Li-containing Only tested on AA2024-T3 Good barrier properties provided by both systems Organic: effective inhibitor is still needed to achieve good corrosion resistance Nanocomposites: higher density of inhibitor can be loaded into the system Nanocomposites: cost towards implementation could be too important 99,100 Phosphate-based Steel carbon steel Al alloys zinc were controllably released from the LDH containers and also that the aggressive chloride ions were also entrapped within such containers.…”
Section: Lithium-containing Coatingsmentioning
confidence: 99%
“…Indeed, rare-earth salts were able to inhibit the corrosion of several systems such as Zn, galvanized steel, Mg, or Al alloys and successfully integrated into primers or conversion coatings. [56][57][58][61][62][63][64] However, the rareearth-based oxides could dissolve in an acidic environment and therefore making this rare-earth-based surface layer less stable or durable, compared to the Cr 2 O 3 layer form using hexavalent chromium. In addition, several studies performed on a coated Al alloy AA2024-T3 reported minor improvement in pitting potential and corrosion current, calling into question the efficacy of Cebased conversion coatings.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in corrosion rate indicates the barrier properties of the cerium oxide/hydroxide films on the steel substrate in a corrosive environment. The deposition mechanism involves both the oxidation of iron and the reduction of H 2 O 2 in the reaction 40 43 reported that during the cerium conversion coatings process, the ceria particle size was increased with the immersion time. They suggested that the increase in the particle size was probably related to an increase in the pH near the surface because the rate of the hydrolysis of cerium ions is increased at a higher pH.…”
Section: Effect Of Immersion Timementioning
confidence: 99%
“…The effect of this microstructural characteristic is an overestimation of the oxide thickness, which has been reported to be about 4 nm [7] and 7 nm. [8] XPS analysis of the passive films formed on nitrogenimplanted alloy XPS depth profile of the N + -implanted alloy (Fig. 4) shows that nitrogen penetrates about 160 nm.…”
Section: Xps Analysis Of the Natural Passive Layer Formed Upon Air Exmentioning
confidence: 99%